2012
DOI: 10.1038/mp.2012.161
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of rare copy number variations reveals PARK2 as a candidate gene for attention-deficit/hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common, highly heritable neurodevelopmental disorder. Genetic loci have not yet been identified by genome-wide association studies. Rare copy number variations (CNVs), such as chromosomal deletions or duplications, have been implicated in ADHD and other neurodevelopmental disorders. To identify rare (frequency ⩽1%) CNVs that increase the risk of ADHD, we performed a whole-genome CNV analysis based on 489 young ADHD patients and 1285 adult population-based co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 48 publications
1
71
3
2
Order By: Relevance
“…A study of 489 ADHD patients and 1285 controls found rare CNVs in the parkinson protein two gene (PARK2) [123]. The result was significant after empirical correction for genome-wide testing.…”
Section: The Search For Rare Genetic Variantsmentioning
confidence: 91%
See 1 more Smart Citation
“…A study of 489 ADHD patients and 1285 controls found rare CNVs in the parkinson protein two gene (PARK2) [123]. The result was significant after empirical correction for genome-wide testing.…”
Section: The Search For Rare Genetic Variantsmentioning
confidence: 91%
“…Because CNVs often delete or duplicate a large genomic segment spanning part of a gene or even entire genes, they often have clear implications for gene functioning. Studies of CNVs in ADHD assessed ADHD youth and controls for the presence of large (>500 kb), rare CNVs [77,[122][123][124][125][126][127]. Each study, except one, found an odds ratio greater than one, indicating a greater burden of large, rare CNVs among ADHD patients compared with controls.…”
Section: The Search For Rare Genetic Variantsmentioning
confidence: 99%
“…A threefold excess of duplications and deletions has been observed in SZ cases (table 7),31 46 and both rearrangements have been implicated in ADHD 48 103…”
Section: Recurrent Cnvs Associated With Increased Risk For Ndsmentioning
confidence: 96%
“…48 103 Among them, the nuclear distribution gene E homologue 1 ( NDE1 ) is of particular interest, because the nudE neurodevelopment protein 1 is essential for mitosis and neurodevelopment, and interacts with the disrupted in SZ 1 protein,105 implicated in SZ and in other major psychiatric disorders 106–108 . NDE1 deficiency impairs neurogenesis, by causing profound neuronal proliferation defects and a deficiency in cortical lamination, as observed in Nde1-null mice and in patients with NDE1 homozygous mutations, who present extreme microcephaly with lissencephaly 106 107.…”
Section: Recurrent Cnvs Associated With Increased Risk For Ndsmentioning
confidence: 99%
“…To identify rare (frequency ≤ 1%) CNVs that increase the risk of ADHD, Jarick et al [23] performed a whole-genome CNV analysis based on 489 young ADHD patients and 1285 adult population-based controls and identified one significantly associated CNV region. In tests for a global burden of large (>500 kb) rare CNVs, they observed a nonsignificant 1.126-fold enriched rate of subjects carrying at least one such CNV in the group of ADHD cases and rare CNVs within the parkinson protein 2 gene (PARK2) with a significantly higher prevalence in ADHD patients than in controls.…”
Section: Phenotypementioning
confidence: 99%